Assessing socio-economic inequalities in the use of antenatal care in the Southern African Development community - Selebano, Keolebogile Mable (Department of Public Health and Family Medicine, 2020)
Introduction Despite the unprecedented efforts of national governments along with various NGOs to achieve the third SDG, which is to reduce global maternal mortality to less than 70 per 100 000 live births by 2030, developing countries seem to be lagging far behind in reaching this goal (UNDP, 2016). This paper focuses on socioeconomic inequalities in the use of ANC services as an important aspect of MHC in SADC countries. Methods The data used in this study are obtained from the Demographic and Health Survey (DHS). Three mutually exclusive variables were created to assess ANC inequality, namely, 1) No ANC visits 2) Less than four ANC visits and 3) At least four ANC visits. A fourth variable that assesses the actual number of ANC visits that a pregnant woman had received was created and called 'Intensity’. ANC and SES using the wealth index were used to construct the concentration curves and indices to determine whether health care utilization is concentrated among the poor or the rich. Results Over 70% of all who lived in rural areas had '0 ANC’, with Namibia and Tanzania as the only exception to this finding. In four of the eleven countries, over 58.36% of women were married and were likely to make an adequate number of ANC visits. Namibia and Lesotho are two of the eleven countries that had a great majority of women educated up to the secondary level, 65.61% and 49.90% of which attained at least 4 ANC visits, respectively. Women who worked in agricultural settings had the least likelihood of attaining any ANC visits. Discussions and conclusion ANC use was consistently lower in women with no education, doing agricultural work and those residing in rural areas in the SADC region. Overall, marriage is inconclusive in determining ANC use. Inequality in wealth makes ANC utilization more predominant among the rich. Saving mothers and babies is ultimately saving the population and knowledge of the patterns of maternal health usage is imperative to draw relevant policies that are evidence based.